Indonesian Tourists’ Perception regarding Singapore’s Tourism Television Commercial - Yusuf, Mohamad; Santoso, Edward Giordan (Binus Business Review, 2020)
The research aimed to highlight the impact of the television commercial (TVC) on Indonesians’ perceptions regarding tourism in Singapore and their behavioral intention to visit Singapore. The research had five variables: hospitality and comfort/security, infrastructures and superstructures, cultural and natural attractions, perceived values, and behavioral intention. It utilized a quantitative method. About 267 samples were collected using a random sampling method. Data analysis was drawn from the mean difference for each variable. The findings indicate that the TVC has positive impacts on the studied variables. The result implies that understanding tourists’ perceptions about Singapore as a travel destination will help the stakeholders to formulate appropriate marketing strategies and position it as a destination choice. However, further research needs to highlight how each variable influences tourists’ behavioral intention to revisit Singapore.